The influence of online education on pre-service teachers’ academic experiences at a higher education institution in the United Arab Emirates - Qiqieh, Sura; Dukmak, Samir (Frontiers in Education, 2024)
Online education has gained widespread adoption in recent years due to several factors, including the COVID-19 pandemic, which has accelerated the growth of online education, with universities transitioning to online platforms to continue their activities. However, this transition has also impacted the preparation of pre-service teachers, who receive training to become licensed or certified teachers. This study investigates the influence of online education on the academic experiences of 130 pre-service teachers attending the Postgraduate Diploma Program at Al Ain University in the UAE. It also explores the relationships between pre-service teachers’ demographics and five academic experiences. A quantitative questionnaire consisting of five newly-developed scales was used for data collection. Pre-service teachers’ demographics were found not to impact effective teaching and learning, skill development, or satisfaction. Age and employment status were found not to influence pre-service teachers’ views of faculty online assessment and feedback or course organization and management. However, online course organization and management and faculty online assessment and feedback were significantly correlated with marital status as engagement and motivation with employment status was, but not with age or marital status. Effective teaching and learning, faculty assessment, and feedback positively impacted pre-service teachers’ engagement and motivation, while effective teaching and learning and course organization correlated with pre-service teachers’ skill development and satisfaction. Research on online education and pre-service teachers’ experiences post-pandemic is limited. Thus, future studies should explore this relationship to understand better pre-service teachers’ online learning experiences, involvement, and success.